Pablo Picasso. - Charles, Victoria (Parkstone International, 2011)
Pablo Picasso is among the most famous figures in 20th-century art, whose works testify to the parallelism of his life and art and underline the impact of important encounters and events. This book assembles a selection of his most extraordinary works, accompanied by insightful texts, and it is the perfect gift for art enthusiasts.